1976
DOI: 10.1063/1.433115
|View full text |Cite
|
Sign up to set email alerts
|

New values of the light scattering depolarization and anisotropy of water

Abstract: A new value for the depolarization ratio of pure water has been measured at 514.5 nm using an argon ion laser light source and photon counting detection. This depolarization ratio is lower than any previous literature value by a substantial amount. Stray light and photometer geometry are shown to be responsible for overestimated values reported previously. The depolarization ratio is also shown to be a function of the portion of the spectrum being investigated. With no filters we find ρv=0.026. The magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…It was also necessary in these extremely clear waters that the ambient water temperature be used in the computation of b bw to achieve the most accurate results. These results support the use of δ=0.051 after Farinato and Roswell (1976). However, since Farinato and Roswell is a single study that lowered a previously accepted constant (Morel, 1974;Shifrin, 1988) by more than 40%, this is certainly a topic that could benefit from additional investigation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It was also necessary in these extremely clear waters that the ambient water temperature be used in the computation of b bw to achieve the most accurate results. These results support the use of δ=0.051 after Farinato and Roswell (1976). However, since Farinato and Roswell is a single study that lowered a previously accepted constant (Morel, 1974;Shifrin, 1988) by more than 40%, this is certainly a topic that could benefit from additional investigation.…”
Section: Discussionmentioning
confidence: 64%
“…However, since Farinato and Roswell is a single study that lowered a previously accepted constant (Morel, 1974;Shifrin, 1988) by more than 40%, this is certainly a topic that could benefit from additional investigation. In fact, Jonasz and Fournier (2007) have recently recommended the use of δ=0.039 based on another interpretation of the data of Farinato and Roswell (1976), highlighting the substantial uncertainty that remains in this constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower values of δ result in lower estimates of scattering (e.g., Jonasz and Fournier, 2007;Twardowski et al, 2007). On the basis of the study by Farinato and Roswell (1975), Jonasz and Fournier (2007) suggested that an adequate value of δ may be as low as 0.039. The theoretical estimates for lower values of δ were also shown to be closer to the experimental estimates of pure water scattering reported in Morel (1974).…”
Section: Inherent Optical Propertiesmentioning
confidence: 99%
“…From Table 1, the depolarization ratios of 405, 430 and 457.9 nm for LAB are the same within 1 σ . It is well known that the depolarization ratio is a weak function of wavelength over the visible range [20,23]. Therefore, we can conclude that the depolarized part of light scattering in LAB is Rayleigh scattering even if we can not directly study the depolarization of light scattering of LAB at 430 nm, the main region of interest, due to the limitation of light source.…”
Section: Resultsmentioning
confidence: 99%